Analisis Pengelolaan Alokasi Dana Desa (ADD) Dalam Upaya Pemberdayaan Dan Peningkatan Kesejahteraan Masyarakat Di Desa Perk.Pulahan Asahan - Ayu Aldira Sari; Nurlaila Nurlaila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Village fund allocations are funds sourced from the APBN for villages which are transferred through the district/city APBD which are used to finance government administration, implementation of development and community empowerment. This research aims to determine the management of village fund allocations in efforts to empower and welfare the community in Perk. Pulahan village based on Government Regulation No.6, 2014. The data analysis technique used in this research is descriptive using qualitative analysis methods. The results of this research show that overall village fund management has been carried out well, but the lack of community participation in this matter means that management is not optimal. Communities are needed to build villages together, because communities have a huge influence on the success of development and the growth of quality communities.